Technological characterisation of probiotic lactic acid bacteria as starter cultures for dry fermented sausages - Agüero, Nadia de Lourdes (2020)
The objective of this study was to investigate probiotic microorganisms for use as starter cultures in dry fermented sausages production. A total of eight strains were studied evaluating technological and safety characteristics including the ability to grow, lactic acid production, gas formation, catalase activity, nitrate reductase activity, proteolytic activity, lipolytic activity, hydrogen peroxide production, salt tolerance, performance at low temperatures, decarboxylation of amino acids and antimicrobial activity against pathogens associated with the product. Lactobacillus rhamnosus R0011, L. rhamnosus Lr-32, Lactobacillus paracasei Lpc-37, Lactobacillus casei Shirota and Enterococcus faecium MXVK29 were good candidates for use as fermented sausages starters cultures because they showed the best technological and safety properties since they did not demonstrate amino acid decarboxylation but showed antimicrobial activity against Listeria monocytogenes, Escherichia coli, Salmonella Dublin and Staphylococcus aureus. L. rhamnosus Lr-32 was the strain best tolerating the levels of salt, nitrate and low pH during the simulated stages of fermentation and ripening of sausage. The strain was thus the most promising of the tested probiotics as sausage starter culture. The findings warrant studies in a meat matrix, such as that of raw-cured sausage, to evaluate the effects of L. rhamnosus Lr-32 under actual conditions.